Construction and configuration of convection-powered asphalt solar collectors for the reduction of urban temperatures - Chiarelli, Andrea; Al-Mohammedawi, A.; Dawson, Andrew; Garcia, Alvaro (Elsevier, 2017)
In this paper, an analysis of a convection-powered asphalt solar collector prototype is approached by the means of experimental trials and computational fluid dynamics (CFD) simulations in order to evaluate how to optimise its design for the reduction of high urban pavement temperatures. Since the energy harvesting setup consists of a series of pipes buried in the pavement, their arrangement is here studied and experimentally compared to a possible construction technique consisting of concrete corrugations that aim at replacing the pipes. CFD simulations are employed to optimise the air collection chamber which is placed immediately before the heated air leaves the asphalt solar collector prototype. The data gathered is analysed in terms of energy harvested and exergy.